PENGARUH FINANCIAL LITERACY, DIGITAL LITERACY, DAN ACCOUNTING MENTAL TERHADAP SUSTAINABILITY UMKM - Aliah Pratiwi; Nurul Huda; Reza Muhammad Rizqi (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The MSME sector is one of the economic drivers, but deep In its current development, there are still many problems that have not yet been discovered resolved, including those related to finance and marketing. The aim of this research is to determine the influence of financial literacy, digital literacy and mental accounting that MSME business actors have on the sustainability of their business among MSME actors in Bima City, NTB. This research is quantitative research. To test the hypothesis and take the population as well as the research sample, namely MSME business actors (managers) from Gen Z in Bima City, a total of 150 respondents. The research results show that financial literacy and mental accounting have an influence on sustainability. Meanwhile, digital literacy has an influence on sustainability. Sektor UMKM menjadi salah satu penggerak perekonomian, namun dalam perkembangannya saat ini masih banyak ditemukan permasalahan yang belum terselesaikan diantaranya terkait bidang keuangan dan pemasaran. Tujuan penelitian ini mengetahui pengaruh dari financial literacy, digital literacy dan accounting mental yang dimiliki pelaku usaha UMKM terhadap keberlangsungan usahanya dari para pelaku UMKM di Kota Bima, NTB. Penelitian ini merupakan penelitian kuantitatif. Untuk menguji hipotesa dan mengambil populasi sekaligus sample penelitian yaitu pelaku usaha (pengelola) UMKM dari Gen Z di Kota Bima sejumlah 150 responden. Hasil penelitian menunjukkan bahwa financial literacy dan accounting mental memberikan pengaruh terhadap sustainability. Sedangkan, digital literacy memberikan pengaruh terhadap sustainability.